Pan Trinbago Needs $600,000 for Festival. - Blood, Peter Ray (Daily Express)
A startling disclosure that this year's Steelband Music Festival - Pan is Beautiful Five: A World Steelband Festival, is still short of more than $600,000 with just eight days left to the Festival. The President of Pan Trinbago, Arnim Smith and the Festival Organizing Committee vice-chairman Bruce Aanansen comment on the matter and disclosed that an appeal has been made to the business sector and the general public.
Keywords: Steel bands (Music) -- Finance -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Music festivals -- Trinidad and Tobago